KUPU-KUPU TERSEMBUNYI PENERUS BANGSA DI TPA SUKAWINATAN - Lisnani, Lisnani; Beda, Maria Oktavia Nira Tania; Manik, Thessalonika Elma La Septi; Lestari, Benediktha Evi Fani Puji; Prasetyo, Titus Dwianto; Angeliana, Wenny (UNIVERSITAS PGRI MADIUN, 2021)
Abstract. Hidden butterfly of the successor to the nation is a form of devotion conducted by students from different study programs with lecturers. This activity was carried out by five students from different study programs namely Primary School Teacher Education, English Education, Management, Accounting, and Industrial Engineering. The purpose of this activity is to equip children of TPA Sukawinatan with the following: 1) improving the ability to read, write and count (calistung); 2) improve English language skills; 3) apply wise attitude in using money; 4) Instilling good character of management (arrangement) and time discipline in children; 5) Developing children's skills in utilizing used goods to be made as something that has added value. The method of implementation used in the form of preparation, planning and implementation stages. Methods of practice, experiments, lectures and games. The results of this activity are as follows: 1) increased ability to read, write and count; 2) increasing English language skills; 3) understanding the importance of using money wisely; 4) has a management character (discipline) of time; 5) have skills in utilizing used goods to become something that has added value.Abstrak. Kupu-kupu tersembunyi penerus bangsa adalah bentuk kegiatan pengabdian yang dilakukan oleh mahasiswa dari program studi berbeda bersama dosen. Kegiatan ini dilakukan oleh lima orang mahasiswa dari program studi yang berbeda-beda yaitu Pendidikan Guru Sekolah Dasar, Pendidikan Bahasa Inggris, Manajemen, Akuntansi, dan Teknik Industri. Tujuan dari kegiatan ini adalah membekali anak-anak TPA Sukawinatan dengan hal berikut: 1) meningkatkan kemampuan membaca, menulis dan berhitung (calistung); 2) meningkatkan kemampuan berbahasa Inggris; 3) menerapkan sikap bijaksana dalam menggunakan uang; 4) Menanamkan karakter manajemen (pengaturan) dan disiplin waktu yang baik pada anak-anak; 5) Menumbuhkembangkan keterampilan anak-anak dalam memanfaatkan barang bekas untuk dijadikan sesuatu yang memiliki nilai tambah. Metode pelaksanaan yang digunakan dalam bentuk tahap persiapan, perencanaan dan pelaksanaan. Metode praktik, eksperimen, ceramah, dan permainan. Hasil dari kegiatan ini adalah sebagai berikut: 1) meningkatnya kemampuan membaca, menulis dan berhitung; 2) meningkatnya kemampuan bahasa Inggris;3) memahami pentingnya penggunaan uang dengan bijak; 4) memiliki karakter manajemen (disiplin) waktu; 5) memiliki keterampilan dalam memanfaatkan barang bekas untuk dijadikan sesuatu yang memiliki nilai tambah.